Designing a science curriculum model based on STEM with an Islamic perspective for 9th Grade - Al-Hidabi, Dawood Abdulmalek Yahya; Abu Owda, Mohammed F. (2019)
The digital age besides the local and global economic changes are challenging the designers, developers, and implementers of the curriculum, as they are the basis for providing students with knowledge, skills and thinking skills to be involved in the society effectively and positively. Consequently, this has led to changes in the philosophy, objectives and teaching methods. STEM is one of the most important approaches of teaching, which attracted the attention of many researchers. Within the framework of this global and regional attention, this paper attempts to provide a model of Science curriculum based on STEM and integrating it with Islamic perspective, in accordance with the Islamic perspective. More particularly, this paper focuses on integrating relevant Qur’anic miracles to STEM curriculum. In this context, the paper presents a developed model for the science curriculum that is based on STEM and Islamic perspective in general for 9th graders.